Using peer education to improve diabetes management and outcomes in a low-income setting: a randomized controlled trial - Seuring, Till; Marthoenis, Marthoenis; Rhode, Sabrina; Rogge, Lisa; Rau, Holger A.; Besançon, Stéphane; Zufry, Hendra; Sofyan, Hizir; Vollmer, Sebastian (Trials, 2019)
Background: Diabetes is an important health burden in Indonesia. However, diabetes management and treatment remain poor, with most people with diabetes in Indonesia not achieving the recommended blood glucose levels. Peer education may have particular potential in low-income settings in complementing diabetes care without being a large additional strain on the health system. Methods/design: This cluster randomized controlled trial aims to identify the effect of the implementation of peer education for patients with type 2 diabetes on diabetes-related outcomes in Aceh, Indonesia, which will complement the diabetes treatment provided at primary-care health posts (puskesmas). Altogether, 29 puskesmas were recruited in Banda Aceh and Aceh Besar, each of which was randomly assigned to either the control or the intervention group. Then, 534 people with diabetes were identified and recruited through their respective puskesmas. The intervention consists of up to two peer education groups per puskesmas, which are led by previously trained people with diabetes. Peer education sessions are held every month for 18 months, with followup data being collected 9 and 18 months after the first peer education session. The main objective is to improve diabetes management and the health behavior of participants receiving peer education to reduce their average blood glucose levels as measured by glycated hemoglobin (HbA1c) levels. Secondary outcomes are the effects of peer education on lipid levels, waist circumference, blood pressure, quality of life, treatment adherence, diabetes knowledge, physical activity, and dietary diversity. Data sources for the measurement of outcomes include patient and health facility surveys and biomarker measurements. An economic evaluation will be conducted to assess the cost-effectiveness of the intervention. Discussion: This trial will contribute to the evidence on the effectiveness and cost-effectiveness of peer education in improving diabetes management in a low-income setting in Indonesia and in other comparable contexts. Trial registration: ISRCTN registry, ISRCTN68253014. Registered on 18 February 2019.
Gesehen am 25.02.2020